Nivel d estrés y su relación con el nivel de rendimiento académico de los alumnos del 4° y 5° grado de nivel secundario de la institución educativa privada Lobachevsky de Trujillo 2013 - Contretas Quiñones, Erika Jannifer (2013)
This quantitative research, descriptive, correlational, cross-sectional had as objective relate the level of stress and the academic performance of students in secondary level of the private educational institution Lobachevsky on Trujillo. The sample consisted of 57 students who answered a questionnaire of academic stress, the results show that: of the total number of students that have a low stress level of the 2.5 % has a regular academic level, a 57.5 % good and 40% excellent; and also of students that has a medium level of stress, the 6.7 % their academic level is regular and a 93.3 % has a good academic level, there is no student with excellent academic level. It is concluded that there is significant relationship between the stress level and academic performance.